2016
DOI: 10.1055/s-0036-1571834
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Spread in Noncutaneous Head and Neck Cancer: New Insights into an Old Problem

Abstract: Head and neck malignancies have the propensity to invade nerves. Perineural tumor invasion is common, with some series reporting rates of 30 to 100%. Squamous cell carcinoma and adenoid cystic carcinoma are the most commonly involved tumors. The most commonly involved nerves are the trigeminal (cranial nerve [CN] V) and facial (CN VII) and their branches. Neural spread away from a tumor is encountered less often and usually causes specific symptoms such as pain, muscle weakness, and atrophy, depending on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 70 publications
1
44
0
Order By: Relevance
“…Some pathologists report tumors in close proximity to nerves and at least one‐third of the nerve circumference as PNI. However, a recent study suggests that tumor invasion into any nerve layer or nerve sheath as clinically relevant PNI . In addition, detection of PNI in a specimen is challenging because of processing artifacts or inadequate specimen assessment leading to false‐negative reporting .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some pathologists report tumors in close proximity to nerves and at least one‐third of the nerve circumference as PNI. However, a recent study suggests that tumor invasion into any nerve layer or nerve sheath as clinically relevant PNI . In addition, detection of PNI in a specimen is challenging because of processing artifacts or inadequate specimen assessment leading to false‐negative reporting .…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study suggests that tumor invasion into any nerve layer or nerve sheath as clinically relevant PNI. 17 In addition, detection of PNI in a specimen is challenging because of processing artifacts or inadequate specimen assessment leading to falsenegative reporting. 18 Although PNI is seen in small peripheral nerves histologically and is clinically silent, perineural spread is the tumor spread along larger nerves clinically or is radiologically evident and often symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature describes a more conclusive role for PNI in prognosis, supplementary data could contribute to discussions about the use of PNI (and perhaps ALI) to guide postsurgical treatment. 17,22,23 …”
mentioning
confidence: 99%
“…We demonstrated a decrease in both OS and DFS when large named nerves were involved on univariate analysis. 25,26 As it seems that microscopic perineural invasion is not reliably associated with survival, future studies may emphasize the prognostic significance of these 2 variables. 13,21 It has been suggested that microscopic perineural invasion loses prognostic significance due to the use of postoperative radiotherapy to sterilize residual microscopic tumor.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although not analyzed in this study, the authors recognize that perineural spread, distinguished from perineural invasion by gross disease spread along nerves, and intraneural invasion have been associated with worse survival. 25,26 As it seems that microscopic perineural invasion is not reliably associated with survival, future studies may emphasize the prognostic significance of these 2 variables.…”
Section: Discussionmentioning
confidence: 99%